Politeness and impoliteness in social network service communication in Korea - Seongha Rhee (Russian Journal of Linguistics, 2023)
With the technological benefits and challenges computer-mediated communication provides, interactants in social network service (SNS) communication are driven to use language creatively, overcoming the disadvantages and exploiting advantages. This creative language use leads to innovative language change that often extends beyond SNS environments. In this regard, the medium is not merely a restrictive but also a facilitative factor. Communicative acts are fundamentally bound by the interactants’ desire to express politeness, especially in face-threatening acts, well articulated in Brown and Levinson’s (1987) model. In recent research, however, the issues of the norms of politeness and impoliteness as well as those of appropriateness have been highlighted (Locher Watts 2005, Locher Bousfield 2008). Interactants employ not only mitigating strategies to alleviate face-threatening but also use impoliteness strategies, which are often disguised politeness. Drawing upon the data from a 26-million-word corpus of synchronous SNS communication, involving two or more participants, in 3,836 instances, developed by the National Institute of the Korean Language, this paper addresses how SNS interactants make use of diverse elements of language to show their polite and impolite stances in interpersonal negotiation. For instance, interactants use fragments, interjections, letter-based ideophones and emoticons, exaggerated punctuations for emotiveness, omission of regular punctuation marks, intentional violation of orthographic rules, prolific slang expressions, deviated spelling to create cuteness or intimacy, among numerous others. All these creative strategies lead to language change at lexical, grammatical and discourse levels.